2020
DOI: 10.1101/2020.06.10.141853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Group and Individual Level Variations between Symmetric and Asymmetric DLPFC Montages for tDCS over Large Scale Brain Network Nodes

Abstract: Two challenges to optimizing transcranial direct current stimulation (tDCS) are selecting between, often similar, electrode montages and accounting for inter-individual differences in response. These two factors are related by how tDCS montage determines current flow through the brain considered across or within individuals. MRI-based computational head models (CHMs) predict how brain anatomy determine electric field (EF) patterns for a given tDCS montage. Because conventional tDCS produces diffuse brain curre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 72 publications
3
14
0
Order By: Relevance
“…up to 2 ms) alternating stimulation of left and right DLPFCs with the SD montage may have induced such inter-hemispheric inhibition in the present study, which could have lead to an absence of behavioral difference with the Sham group. This superiority of unilateral over bilateral montage has been previously observed in a tDCS methodological article 65 . The authors measured a higher electrical dose within the targeted DLPFC and also within the connected network nodes (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…up to 2 ms) alternating stimulation of left and right DLPFCs with the SD montage may have induced such inter-hemispheric inhibition in the present study, which could have lead to an absence of behavioral difference with the Sham group. This superiority of unilateral over bilateral montage has been previously observed in a tDCS methodological article 65 . The authors measured a higher electrical dose within the targeted DLPFC and also within the connected network nodes (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…No significant results were found within the other networks. The main resons for finding significant associations only in ECN and DMN (and not other brain networks) might be related to strong EFs in these two networks [32].…”
Section: Discussionmentioning
confidence: 94%
“…One of the factors limiting the therapeutic potential of tDCS is the high inter-subject variability of behavioural effects. It has been suggested that this might, at least in part, be due to the use of a standard extracranial current intensity across participants, which will inevitably lead to variability in the E-field applied in the cortex (Abellaneda-PĂ©rez et al, 2020; Kim et al, 2014; Laakso et al, 2015; Mezger et al,2021; Soleimani et al, 2021). Supporting this theory, tDCS-induced behavioural outcomes such as improvements in working memory have been related to the applied E-field (Albizu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%